Surgical treatment of melanoma in pregnancy: a practical guideline. (30th May 2016) - Crisan, Diana; Treiber, Nicolai; Kull, Thomas; Widschwendter, Peter; Adolph, Oliver; Schneider, Lars Alexander
Summary: A tumor primarily requiring surgical treatment, newly diagnosed or preexisting melanoma during pregnancy is a clinical rarity. In such cases, the surgeon faces the challenge of having to decide on the appropriate therapeutic course of action. Based on our clinical experience and a review of the literature, we herein provide a guideline on how to practically deal with this rare clinical conundrum. In our experience, pregnant melanoma patients require thorough counseling with respect to their therapeutic options. They naturally tend to put their unborn child first, and are hesitant to consent to necessary surgery despite a potentially life‐threatening diagnosis. It is therefore crucial to clearly inform these patients that – based on existing medical experience – pregnancy by itself is no reason to hold off on any type of necessary melanoma surgery. However, various parameters such as preoperative imaging procedures, positioning on the operating table, monitoring, anesthesia, and perioperative medication require certain adjustments in order to comply with this special situation.